(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is about the effective ways to use the opportunities of infographics in the work of future informatics and information technology teachers, the concept of infographics and its types are covered in detail, and the article also provides information about several of the most popular platforms in the field of infographics.